The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1516-14392013005000032
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis in ultrafine grained coppers processed by equal channel angular pressing

Abstract: Electrolytic tough pitch (ETP) and fire refined high conductivity (FRHC) copper samples were severely deformed at room temperature by equal channel angular pressing (ECAP) up to 16 passes (ε ~ 1 per pass), following route Bc. The effect of the initial texture on the evolution of texture after the ECAP process for both materials was analyzed. The annealed materials present a marked anisotropy, with a texture controlled by the <110> fiber. According to the orientation distribution function (ODF), this initial be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…4, the ODF is only at ϕ = 0° and ϕ = 45° for the sequence of number of ECAP passes in the route A and Bc in the ambient temperature condition. As can be seen, using the ODF of cold processed samples by ECAP, the texture presented by the evolution of passes through route A, it was found that right after the first pass, the Brass component (B) (110) [11 2] appeared of recrystallization texture and after the second pass, the components C (001) [ It can be said that the results obtained are following those found in the literature, as can be seen in the research carried out by Higuera and Cabrera [20]. They processing copper by ECAP via the Bc route at ambient temperature and demonstrated that after the first pass was carried out, the material preferentially exhibited deformed fiber B, due to a high proportion of component C with a moderate presence of components B/𝐵 and A/𝐴 ̅ .…”
Section: Cold Ecap -Route a And Bcsupporting
confidence: 62%
“…4, the ODF is only at ϕ = 0° and ϕ = 45° for the sequence of number of ECAP passes in the route A and Bc in the ambient temperature condition. As can be seen, using the ODF of cold processed samples by ECAP, the texture presented by the evolution of passes through route A, it was found that right after the first pass, the Brass component (B) (110) [11 2] appeared of recrystallization texture and after the second pass, the components C (001) [ It can be said that the results obtained are following those found in the literature, as can be seen in the research carried out by Higuera and Cabrera [20]. They processing copper by ECAP via the Bc route at ambient temperature and demonstrated that after the first pass was carried out, the material preferentially exhibited deformed fiber B, due to a high proportion of component C with a moderate presence of components B/𝐵 and A/𝐴 ̅ .…”
Section: Cold Ecap -Route a And Bcsupporting
confidence: 62%